1992
DOI: 10.1002/eji.1830220606
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial heat‐shock proteins as carrier molecules. II: The use of the 70‐kDa mycobacterial heat‐shock protein as carrier for conjugated vaccinescan circumvent the need for adjuvants and Bacillus Calmette Guérin priming)

Abstract: In a recent work, we have shown that mycobacterial heat-shock proteins (hsp) of 65-kDa (GroEL-type) and 70-kDa (DnaK-type) acted as carrier molecules in mice, previously primed with Mycobacterium tuberculosis var. bovis (bacillus Calmette-Guérin, BCG), for the induction of high and long-lasting titers of IgG against the repetitive malaria synthetic peptide (NANP)40. Anti-peptide antibodies were induced when the malaria peptide, conjugated to the mycobacterial hsp, was given in the absence of any adjuvants (Lus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 48 publications
8
52
0
3
Order By: Relevance
“…This is supported by a previous report that inhibition of another HSP (HSP90) abrogated inflammasome formation (34). It is noteworthy that there is a great deal of evidence that exogenous HSP70 acts as an adjuvant (35)(36)(37)(38), which has been marred by criticism that the HSP70 used may have been contaminated with LPS, flaggelin, or nucleotides (39). This critique cannot be applied to the present work as exogenous HSP70 has not been used, but endogenous, inducible HSP70 was up-regulated by alum.…”
Section: Discussionsupporting
confidence: 68%
“…This is supported by a previous report that inhibition of another HSP (HSP90) abrogated inflammasome formation (34). It is noteworthy that there is a great deal of evidence that exogenous HSP70 acts as an adjuvant (35)(36)(37)(38), which has been marred by criticism that the HSP70 used may have been contaminated with LPS, flaggelin, or nucleotides (39). This critique cannot be applied to the present work as exogenous HSP70 has not been used, but endogenous, inducible HSP70 was up-regulated by alum.…”
Section: Discussionsupporting
confidence: 68%
“…Mycobacterial heat shock protein 70 (MTBHSP70) has a number of immunological properties. It has been shown to be an excellent adjuvant for antibody production [6], as well as an extremely powerful antigen, even in lipopolysaccharide (LPS) hyporesponsive mice [7]. Finally, immunization with MTBHSP70 has been shown to protect against adjuvant arthritis in rats [8].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis may be in line with the adjuvant properties showed by several microbial Hsps. In particular, it has been demonstrated that immunization with peptides or oligosaccharides conjugated to the Mycobacterium tuberculosis Hsp70 promotes a strong humoral response in the absence of adjuvants (Barrios et al 1992). Suzue and Young (1996) have further shown the immunogenic potential of M tuberculosis Hsp70 by immunizing mice with a recombinant human immunodeficiency virus type 1 p24-Hsp70 fusion protein.…”
Section: Introductionmentioning
confidence: 99%